Drip-irrigation systems for small conventional vegetable farms and organic vegetable farms - Eric Simonne; Robert Hochmuth; Jacque Breman; William Lamont; Danielle Treadwell; Aparna Gazula (EDIS)
HS-1144, a 28-page illustrated fact sheet by Eric Simonne, Robert Hochmuth, Jacque Breman, William Lamont, Danielle Treadwell, and Aparna Gazula, presents the principles behind drip irrigation and some practical guidelines for successful and profitable use of drip irrigation for vegetable production in Florida. Includes references. Published by the UF Department of Horticultural Sciences, June 2008.